Finding evidences on oncohematological patients (3rd part): nutrition assessment, nauseas and vomiting - Natalia Lorenzo García; María Dolores Sánchez Ayala; Cristóbal Meseguer Liza; José María Estrada Lorenzo; Lourdes Zarate Riscal; Antonio Paredes Sidrach de Cardona; Eva Abad Corpa (NURE Investigación, 2009)
Introduction: It would be advisable to change cares based in tradition for evidence-based ones. So diffusion of investigation result should be the first step to get this change. Frequently oncologic patients suffer from nauseas and vomiting due to chemotherapy. These symptoms are frequently underestimated by health professionals. Another significant problem is under nourishment, because the relationship between that and worse prognosis is well known. Consequently, our objective has been: to find and summarize the evidences about nauseas and vomiting and the nutrition assessment. Method: Databases as CINAHL, MEDLINE, Cochrane Library, EMBASE, Pascal Biomed, LILACS, CUIDEN, CUIDEN qualitative y CUIDATGE were revised in Spanish, French and English. No time restrictions were applied.Results: The main findings and recommendations were synthesised on a poster, next to suggestions for practical changes to implement, evidence levels used, and the clinic problem significance. The suggested changes arose from nursing staff based on evidences found that includes behaviours and attitudes changes, which should facilitate more rapid innovations diffusion.